Betel leaf toothpastes inhibit dental plaque formation on fixed orthodontic patients - Rizka Amelia Mayasari; Sianiwati Goenharto; Ahmad Sjafei (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2011)
Background: Brackets, archwires, ligatures, and other fixed orthodontic appliance components complicate the use of conventional oral-hygiene measures. This often results in significant plaque accumulation around the bracket bases. The addition of betel leaf extract in toothpaste is expected to inhibit the growth of dental plaque. Purpose: The purpose of this study was to evaluate the effect of betel leaf toothpaste in inhibiting plaque formation on the fixed orthodontic patients. Methods: This study was done on dental student of Airlangga University aged 18–24 years, have been wearing fixed orthodontic appliances for 1–2 years, have no systemic diseases. The samples were divided into two groups, consisting of 20 samples. First group of samples brushed their teeth with betel group of samples brushed their teeth with betel brushed their teeth with betel leaf toothpaste and the second using placebo. The subjects were instructed to brush their teeth using Scrub method until reaching zero (0) scor of orthodontic plaque index (OPI). Plaque scores were taken again 4 hours after brushing. The statistical analysis was done by using paired t test. Results: The average of accumulated plaque on group that use betel leaf toothpaste was 25.54 and placebo was 41.09. The result showed that there was significant difference in plaque accumulation between the group with betel leaf toothpaste and placebo 4 hours after brushing (p = 0.001). Conclusion: In conclusion, betel leaf toothpaste is effective in inhibiting the dental plaque formation on the fixed orthodontic patients. Latar belakang: Bracket, kawat busur, kawat ligatur dan komponen peranti ortodonti cekat yang lain mempersulit pembersihan gigi secara konvensional. Hal ini sering menyebabkan terjadinya akumulasi plak di sekitar dasar braket. Penambahan ekstrak daun sirih yang mempunyai efek bakterisid pada pasta gigi diharapkan dapat menghambat pertumbuhan plak. Tujuan: Tujuan penelitian ini adalah untuk mengevaluasi efek pasta gigi mengandung ekstrak daun sirih dalam menghambat pembentukan plak pada pemakai peranti ortodonti cekat. Metode: Penelitian dilakukan pada mahasiswa Fakultas Kedokteran Gigi Universitas Airlangga berusia 18–24 tahun, sudah memakai peranti cekat ortodonti selama 1–2 tahun, tidak mempunyai penyakit sistemik. Sampel dibagi dalam dibagi dalam dua kelompok, masing-masing 20 sampel. Sampel kelompok pertama menyikat gigi dengan pasta gigi yang mengandung daun sirih dan kelompok kedua dengan pasta gigi placebo memakai metode Scrub. Pembersihan gigi dilakukan sampai didapatkan skor nol (0) Pembersihan gigi dilakukan sampai didapatkan skor nol (0) didapatkan skor nol (0) orthodontic plaque index. Empat jam setelah itu skor plak diukur kembali. Data dianalisis dengan uji T berpasangan. dianalisis dengan uji T berpasangan. Hasil: Rerata pengumpulan plak pada pemakai pasta gigi mengandung daun sirih adalah 25,54 dan placebo adalah 41,09. Analisis data menunjukkan adanya perbedaan bermakna antara kedua kelompok (p = 0,001). Kesimpulan: Dapat disimpulkan bahwa pasta gigi mengandung daun sirih efektif dalam menghambat pertumbuhan plak pada pemakai peranti ortodonti cekat.